Driving Public Service Quality through Innovation and CRM: A Study of Perumda Air Minum Tirta Pakuan, Bogor - Rabbani, Ahmad Dzaki; Slamet, Alim Setiawan; Munandar, Jono Mintarto; Hidayatulloh, Furqon Syarief (SMART Insight, 2025)
Evaluating public service quality is fundamental in measuring the performance of government institutions, particularly in sectors regulated by law. One of the most vital infrastructure services is the provision and management of clean water by regional water utilities. This study focuses on Perumda Air Minum Tirta Pakuan in Bogor City, a benchmark utility expected to exemplify innovation and high-quality service delivery. The research investigates the influence of innovation and customer relationship management (CRM) on service quality and formulates strategic recommendations. A mixed-methods approach was employed, combining descriptive statistics, Structural Equation Modeling–Partial Least Squares (SEM-PLS), and SWOT analysis. The study involved 140 customer respondents and five experts. Findings confirm that innovation and CRM have a positive and significant effect on service quality, with CRM also positively influencing innovation. Based on these insights, a growth and development strategy is recommended to strengthen Tirta Pakuan’s service excellence.